ENDOCRINE TUMOURS: Calcitonin in thyroid and extra-thyroid neuroendocrine neoplasms: the two-faced Janus. Issue 6 (December 2020) - Giannetta, Elisa; Guarnotta, Valentina; Altieri, Barbara; Sciammarella, Concetta; Guadagno, Elia; Malandrino, Pasqualino; Puliani, Giulia; Feola, Tiziana; Isidori, Andrea M; Colao, Annamaria Anita Livia; Faggiano, Antongiulio; ,
Abstract : An increased calcitonin serum level is suggestive of a medullary thyroid cancer (MTC), but is not pathognomonic. The possibility of false positives or other calcitonin-secreting neuroendocrine neoplasms (NENs) should be considered. Serum calcitonin levels are generally assessed by immunoradiometric and chemiluminescent assays with high sensitivity and specificity; however, slightly moderately elevated levels could be attributable to various confounding factors. Calcitonin values >100 pg/mL are strongly suspicious of malignancy, whereas in patients with moderately elevated values (10–100 pg/mL) a stimulation test may be applied to improve diagnostic accuracy. Although the standard protocol and the best gender-specific cut-offs for calcium-stimulated calcitonin are still controversial, the fold of the calcitonin increase after stimulation seems to be more reliable. Patients with MTC show stimulated calcitonin values at least three to four times higher than the basal values, whereas calcitonin-secreting NENs can be distinguished from a C-cell disease by the absence of or <two-fold response to stimulation. The measurement of calcitonin in fine-needle aspirate washout (FNA-CT) and calcitonin immunocytochemical staining from thyroid nodules are ancillary methods that may significantly improve MTC diagnosis. The present review examines the gray areas in the interpretation of calcitonin measurement in order to provide a tool to clarify the origin of calcitonin secretion and differentiate the behavior of the two-faced Janus of neuroendocrinology: intra-thyroid (MTC) and extra-th9yroid NENs.